Diagnostic challenges in meningioma - Nowosielski, Martha; Vollmuth, Philipp; Deimling, Andreas von; Bendszus, Martin; Wick, Wolfgang; Sahm, Felix (Neuro-Oncology, 2017)
This review highlights the diagnostic challenges of meningiomas from both the neuroimaging as well as the neuropathological side and presents the latest scientific achievements and studies potentially helping in overcoming these challenges. It complements the recently proposed European Association of Neuro-Oncology guidelines on treatment and diagnosis of meningiomas by integrating data on nonstandard imaging and molecular assessments most likely impacting the future.